Development of gene manipulation systems for green microalga (Ankistrodesmus convolutus corda.) - Thanh, Tran (2012)
Green microalga Ankistrodesmus convolutus is a fast growing alga which produces appreciable amount of carotenoids and polyunsaturated fatty acids. In addition of the ease and cost-effectiveness of culture, the ability of A. convolutus to form floating aggregates during its normal growth facilitate harvesting and other beneficiary attributes making it an interesting candidate for many biotechnological applications such as production of natural products or expression of recombinant proteins. However, the lack of efficient genetic transformation systems has been a major limitation in the manipulation of green microalgae. The present study provides, for the first time, information on molecular manipulation in A. convolutus, which covered the isolation of nucleic acids, construction of eDNA library and generation of ESTs, cloning and characterization of a highly-expressive eDNA and its promoter towards the establishment of an alternative expression system using A. convolutus. Green microalga Ankistrodesmus convolutus was collected from axenic freshwater, grown and maintained in bold's basal medium. A. convolutus is typically rich in lipids and polysaccharides, which make it difficult to get the intact RNA of high quality and quantity suitable for molecular research on this alga. In an effort to develop a suitable RNA extraction procedure for A. convolutus, a rapid, relatively non-toxic and effective method was finalized. This procedure was able to produce high quality and intact RNA which was of sufficient quality and suitable for downstream application such as RT-PCR, northern hybridization and cDNA library construction. The developed procedure may also have wider applicability for total RNA isolation from other green microalgae species. In order to provide a robust sequence resource that can be exploited for gene discovery, genome annotation and comparative genomics, a cDNA library of A. convolutus was constructed and . preliminarily analysed. A total of 415 randomly selected clones were isolated from the primary cDNA library from which 201 high quality ESTs were produced after the sequencing of337 clones. Among these ESTs, 21.4% of them were found to be related to gene expression, 14.4% to photosynthesis, 10.9% to metabolism, 5.5% to miscellaneous, 2.0% to stress response, and the remaining 45.8% were classified as novel genes. Due to the relatively high abundance, the full-length cDNA of ribulose-l,5-bisphosphate carboxylase/oxygenase (Rubisco) small subunit (RbcS) which was classified into photosynthetic cDNA clone category was selected for further studies. Rubisco is currently the target enzyme for improving the efficiency of photosynthesis in the hope of increasing the yield and growth of crops and henceforth green algae. In this study, the full-length of A. convolutus RbcS cDNA (AcRbcS) contained an open reading frame of 165 amino acids. This cDNA encoded a protein with expected molecular weight of -21 kD sharing high homology with corresponding protein from other microalgae. Southern hybridization analysis revealed that AcRbcS is a member of a small multi gene family comprising of two to six members in A. convolutus genome. Under different illumination conditions, RTPCR analysis showed that AcRbcS transcription was reduced in the dark, and drastically recovered in the light condition. As a primary step to investigate the use of A. convolutus as an alternative expression system for the production of recombinant proteins, the AcRbcS promoter region was isolated through PCR-based methods including ligation-mediated PCR and thermal asymmetric interlaced (TAIL)-PCR. In comparison with the ligation-mediated PCR technique, TAIL-PCR has proven to be an economic, efficient and rapid method to isolate AcRbcS promoter region. The AcRbcS promoter sequence was then analyzed and later used to construct an expression vector for expression of heterologous genes in A. convolutus. The . transcription start site (TSS), consensus TATA-box and several putative cis-acting elements of representative light-regulatory as well as conserved motifs involved in light responsiveness were found in AcRbcS promoter region. The expression vector containing AcRbcS promoter and J3-glucuronidase (gusA) reporter gene were constructed and introduced into A. convolutus cells by electroporation. As a result, transgenic A. convolutus lines was successfully generated and shown to contain the transgenes by PCR and southern hybridization analysis. It was also demonstrated that the AcRbcS promoter could function as a light-regulated promoter in transgenic A. convolutus as shown in northern hybridization analysis. The results presented here represent the initial success on molecular manipulation of green microalgae A. convolutus, which has great potentials to become an interesting and excellent candidate for many biotechnological applications. The achievements therefore advance the development of A. convolutus as an alternative expression system, and it is now feasible that this alga can be examined as an alternative host for the expression of recombinant proteins.